Anatomy and microsurgical relevance of the outer arachnoid envelope around the olfactory bulb based on endoscopic cadaveric observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Adib, Sasan Darius; Barany, Laszlo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background: Surgical approaches to the anterior cranial fossa have great risk of damaging the olfactory tract and bulb. The goal of this study was to describe the outer arachnoid envelope around the olfactory bulb which plays significant role in the approach-related injury of the nerve. Material and Methods: A total of 20 fresh human cadaveric heads were examined as a following: 5 cadaveric heads were used to describe a gross overview of the topographic anatomy of the outer arachnoid cover of the olfactory bulb. In 15 cadaveric heads endoscopic surgical approaches were performed to examine the in situ undisrupted anatomy of the outer arachnoid around the olfactory bulb. Four cadaveric heads were used for lateral subfrontal approach, 5 heads for medial subfrontal, 3 heads for median subfrontal approach and 3 heads for anterior interhemispheric approach. Results: The outer arachnoid membrane of the frontal lobe attaches the olfactory bulb strongly to the above lying olfactory sulcus. Only the most rostral portion of the olfactory bulb became slightly detached from the frontal lobe. The outer arachnoid forms a decent protrusion around the tip of the olfactory bulbs. The fila olfactoria have their own outer arachnoid cover as a continuation of the same layer of the olfactory bulb. The effect of brain retraction and manipulation forces on the olfactory bulb and the role of the here located arachnoid membranes were visually analysed and described in detail through the performed four different neurosurgical approaches. Conclusion: The results of our observations provide important anatomical details for the preservation of smelling during neurosurgical procedures.
CRIS-Team Scopus Importer:2024-12-16
Keywords: arachnoid membranes; endoscopic anatomy; microsurgical anatomy; olfactory bulb

Microsurgical anatomy and pathoanatomy of the outer arachnoid membranes in the cerebellopontine angle: cadaveric and intraoperative observations - Kurucz, Peter; Ganslandt, Oliver; Buchfelder, Michael; Barany, Laszlo (Acta Neurochirurgica, 2023)
Purpose: The cerebellopontine angle (CPA) is a frequent region of skull base pathologies and therefore a target for neurosurgical operations. The outer arachnoid is the key structure to approach the here located lesions. The goal of our study was to describe the microsurgical anatomy of the outer arachnoid of the CPA and its pathoanatomy in case of space-occupying lesions. Methods: Our examinations were performed on 35 fresh human cadaveric specimens. Macroscopic dissections and microsurgical and endoscopic examinations were performed. Retrospective analysis of the video documentations of 35 CPA operations was performed to describe the pathoanatomical behavior of the outer arachnoid. Results: The outer arachnoid cover is loosely attached to the inner surface of the dura of the CPA. At the petrosal surface of the cerebellum the pia mater is strongly adhered to the outer arachnoid. At the level of the dural penetration of the cranial nerves, the outer arachnoid forms sheath-like structures around the nerves. In the midline, the outer arachnoid became detached from the pial surface and forms the base of the posterior fossa cisterns. In pathological cases, the outer arachnoid became displaced. The way of displacement depends on the origin of the lesion. The most characteristic patterns of changes of the outer arachnoid were described in case of meningiomas, vestibular schwannomas, and epidermoid cysts of the CPA. Conclusion: The knowledge of the anatomy of the outer arachnoid of the cerebellopontine region is essential to safely perform microsurgical approaches as well as of dissections during resection of pathological lesions.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Arachnoid; Cerebellopontine angle; Epidermoid cyst; Meningioma; Surgical anatomy; Vestibular schwannoma

Topographical anatomy of the septum verum and its white matter connections - Barany, Laszlo; Meszaros, Cintia; Alpar, Alan; Ganslandt, Oliver; Hore, Nirjhar; Delev, Daniel; Schnell, Oliver; Kurucz, Peter (Scientific Reports, 2024)
The human septum verum represents a small but clinically important region of the brain. Based on the results of animal experiments, the stimulation of its medial part was recently proposed with various indications like epilepsy or cognitive impairment after traumatic brain injury. The aim of our study was to present the anatomical relationships of the human septum verum using fiber dissection and histological analysis to support its research and provide essential information for future deep brain stimulation therapies. 16 human cadaveric brains were dissected according to Klingler’s method. To validate our macroscopical findings, 12 samples obtained from the dissected brains and 2 additional specimens from unfrozen brains were prepared for histological examinations. We identified the following white matter connections of the septum verum: (1) the precommissural fibers of the fornix; (2) the inferior fascicle of the septum pellucidum; (3) the cingulum; (4) the medial olfactory stria; (5) the ventral amygdalofugal pathway; (6) the stria medullaris of the thalamus and (7) the stria terminalis. Moreover, we could distinguish a less-known fiber bundle connecting the postcommissural column of the fornix to the stria medullaris of the thalamus and the anterior thalamic nuclei. In this study we present valuable anatomical information about this region to promote safe and effective deep brain stimulation therapies in the future.
CRIS-Team Scopus Importer:2024-08-16